Firms' Financing Behavior: A Look into Shariah-Compliant Construction Firms in Malaysia - Faizah Ismail; Norhafiza Nordin; Zaemah Zainuddin (International Journal of Economics and Financial Issues, 2016)
This paper examines the financing patterns of 30 Malaysian shariah-compliant construction firms listed on Bursa Malaysia for a period from 2007 to 2014. It retraces the financing patterns of the firms during the sample period to identify whether some patterns can be linked to the economic cycles. Our observation on the firms' financing behaviour supports the mixed evidence on the consistency of capital structure theory. Nonetheless, this study claims an association between financing behaviour and economic sentiments. Albeit not being able to explain the capital structure decision during economic downturn, the study did reveal that firms do prefer debt to equity in the economic revival phase, and prefer to use combination financing in a cautious unpredictable economy. There is apparent evidence that firms' financing behaviour and economic sentiments are very much related. This action corresponds with investors' preference that generally chooses less risky investments during period of high economic uncertainties.